Disrupted balance between pro-inflammatory lipid mediators and anti-inflammatory specialized pro-resolving mediators is linked to hyperinflammation in patients with alcoholic hepatitis - Li, Wei; Xia, Ying; Yang, Jing; Sanyal, Arun J.; Shah, Vijay H.; Chalasani, Naga P.; Yu, Qigui (Frontiers in Immunology, 2024)
BackgroundAlcoholic hepatitis (AH) is characterized by intense systemic and liver inflammation, posing significant risks of health complications and mortality. While inflammation is a crucial defense mechanism against injury and infection, its timely resolution is essential to prevent tissue damage and restore tissue homeostasis. The resolution of inflammation is primarily governed by specialized pro-resolving mediators (SPMs), lipid metabolites derived from w-6 and w-3 poly-unsaturated fatty acids (PUFAs). Currently, the balance between pro-inflammatory lipid mediators (PLMs) and SPMs in the w-6 and w-3 PUFA metabolic pathways and the impact of alcohol abstinence on profiles of PLMs and SPMs in AH patients are not well studied.MethodsIn this study, we used LC-MS/MS and ELISA to quantify levels of lipid mediators (LMs) and their precursors in the plasma samples from 58 AH patients, 29 heavy drinkers without overt liver diseases (HDCs), and 35 healthy controls (HCs). Subsequently, we assessed correlations of altered LMs with clinical parameters and inflammatory mediators. Furthermore, we conducted a longitudinal study to analyze the effects of alcohol abstinence on LMs over 6- and 12-month follow-ups.ResultsAH patients exhibited significantly higher plasma levels of w-6 PLMs (PGD2 and LTB4) and SPM RvE1 compared to HDCs or HCs. Conversely, the SPM LXA4 was significantly downregulated in AH patients. Some of these altered LMs were found to correlate with AH disease severity and various inflammatory cytokines. Particularly, the LTB4/LXA4 ratio was substantially elevated in AH patients relative to HDCs and HCs. This altered ratio displayed a positive correlation with the MELD score. Importantly, the majority of dysregulated LMs, particularly PLMs, were normalized following alcohol abstinence.